KEDUDUKAN NOTARIS DALAM PEMBUKTIAN SUATU PERKARA - Sandra Irawan (Paulus Law Journal, 2022)
Development of a notary position in a case, to find out the existence of a notary in Indonesia is in accordance with positive law and to determine the notary step if it is later that a case will be faced by a notary and to assist the notary public whose incidentals are officials a law known to arise because of the need for mutual relations requires a fellow human being, who wants an instrument of evidence for him regarding the legal relationship between the silvery that exists and / or occurs between them, an institution with its authority assigned by general powers which by law requires so or is desired by the public, making written evidentiary instruments with perfect provisions. The research methodology used is normative juridical research, that is, the author conducts legal research by studying library material or secondary information in the form of various kinds of literature. The conclusion of this study is notary position to explain based on the minuta of the deed carried, the authentic deed which is the basis of the court is the deed which is made based on its authority and signed by both parties who are litigating. Keywords: Notary Position; Proof of Case; Notary; Law